Detection of Y Chromosome Azospermia Factor Microdeletions with Polymerate Chain Reaction in Testicular Azospermic Men - ULUĞ, Murat; SÜSLEYİCİ DUMAN, Belgin and ARVAS ULUĞ, Ayşe and ÇAMLIBEL, Teksen (Cerrahpaşa Medical Journal, 2019)
Y chromosome deletions are associated with severe male factor infertility. A significant role of the Y chromosome in spermatogenesis was established with karyotype and cytogenetic analysis. Deletions in the long arm distal region of the Y chromosome are known to prevent spermatogenesis. This region has been found to be effective in the regulation of spermatogenesis and named as azospermia factor (AZF). This study has investigated the presence of AZF microdeletions of Y chromosome in 45 men with azospermia, oligozoospermia and normozoospermia by using polimerase chain reaction method. In order to search Y chromosome microdeletions, 2 spesific sequence tagged sites (STS) were studied from AZFa, AZFb and AZFc regions. The analyzed STS regions were sY84 and sY86 for AZFa, sY127 and sY134 for AZFb and sY254 and sY255 for AZFc. Results. In the azospermic group one man was found to have 400 bp sY254 (AZFc), whereas two were found to have 126 bp sY255 (AZFc) microdeletions. In men with oligozoospermia and normozoospermia none of the STS region microdeletions was detected. Conclusion. Our results demonstrate that genetic factors may influence sperm production in infertile men and Y chromosome microdeletions may cause infertility in men with azospermia.